2011
DOI: 10.1037/a0025857
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of elder sibling closeness in predicting younger sibling substance use: Social learning versus social bonding explanations.

Abstract: Adolescent siblings are often similar in a variety of adjustment outcomes, yet little is known about the processes that explain sibling influences during adolescence. Two alternative explanations were tested, attachment (based in social bonding theory) and anaclitic identification (based in social learning theory). Hypotheses were tested using a sample of 613 adolescent sibling pairs (206 non-adopted, 407 adopted; elder sibling Mage = 16.1, younger sibling Mage = 13.8) across three sibling contexts (gender com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 46 publications
1
33
0
2
Order By: Relevance
“…This suggests that these associations were at least in part attributable to shared genes, particularly the relationship between sibling tobacco use and EXT (because the group difference was signifi cant). This is not surprising given that adolescent siblings are often similar in their adolescent substance use (Low et al, 2012;Rowe and Gulley, 1992;Samek and Rueter, 2011;Whiteman et al, 2013) and that the link between adolescent substance use and subsequent substance use disorders in adulthood has been shown to be primarily infl uenced by genetic factors (Agrawal et al, 2009;Sartor et al, 2009). Of note, the overall pattern of family environmental effects in relation to adult EXTs differed for parental and sibling environments, demonstrating the need to partial these unique family environments in applications of the hierarchical model of family environmental risk as proposed by Bailey et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that these associations were at least in part attributable to shared genes, particularly the relationship between sibling tobacco use and EXT (because the group difference was signifi cant). This is not surprising given that adolescent siblings are often similar in their adolescent substance use (Low et al, 2012;Rowe and Gulley, 1992;Samek and Rueter, 2011;Whiteman et al, 2013) and that the link between adolescent substance use and subsequent substance use disorders in adulthood has been shown to be primarily infl uenced by genetic factors (Agrawal et al, 2009;Sartor et al, 2009). Of note, the overall pattern of family environmental effects in relation to adult EXTs differed for parental and sibling environments, demonstrating the need to partial these unique family environments in applications of the hierarchical model of family environmental risk as proposed by Bailey et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Trim and colleagues (2006), for example, found that older sibling alcohol use positively influenced younger sibling alcohol use, but only among sibling pairs with a low age gap. Samek and Reuter (2011) also found that siblings less than 1.5 years apart in age were more similar in substance use behavior than those with a wider age gap. Similarly, McHale et al (2009) found that the correlations between the risky sexual attitudes of older and younger siblings were stronger when siblings were close in age and stronger when siblings reported closer relationships.…”
Section: Introductionmentioning
confidence: 78%
“…The sibling closeness moderator has not been fully supported by the literature. Samek and Reuter (2011) found that sibling closeness and older sibling substance use did not interact to predict younger sibling substance use.…”
Section: Introductionmentioning
confidence: 86%
“…Several studies have found that warmth and closeness in sibling relationships increase the likelihood of substance use and sexual behaviors if one sibling already engages in such behavior (McHale et al, 2009;Slomkowski et al, 2005), but limits likelihood of deviant behavior if siblings don't engage (Samek et al, 2011). If one sibling exhibits aggressive behavior toward their sibling, this may also lead to externalizing problems (Natsuaki et al, 2009).…”
Section: Sibling Relationships and Deviancymentioning
confidence: 99%